REVIEW OF BEARING CAPACITY AND SETTLEMENT OF PILE FOUNDATION IN PORT INFRASTRUCTURE - Adi Sunarno; Rinda Karlinasari; Abdul Rochim (UNISSULA Semarang, 2018)
ABSTRACTThe rapid infrastructure development is one of the indicators on the country economic progress. Indonesia as one of the largest archipelagic countries in the world, should be prioritized the port infrastructure to support the maritime. One of the government’s solutions is infrastructure development of Kuala Tanjung port. This research analyzed bearing capacity and settlement of single and group pile foundation on port infrastructure of Kuala Tanjung so it is known that the port is safe to use. The data used are Standard Penetration Test data with soil stratigraphy that is clay and sand. The type of foundation used is Concrete Spun Pile 1000 mm and 600 mm with a pile length of 36 meters. The data are then analyzed by manual calculation and Allpile 6.5E program based on Reese method and methods such as Vesic and Converse-Labarre. The results showed that single pile foundations of 1000 mm and 600 mm each had allowable capacity (Qall) 492.78-538.81 ton and 110.65-128.31 ton, with vertical load (Q) of 330.90 ton, settlement 0.56-1.17 cm and 3.32-3.64 cm, lateral deflection 27.50 cm and 94.90 cm. While the 1000 mm and 600 mm pile group foundations respectively have Qall 8717.31-10796.29 tons and 2059.25-2566.32 tons, with Q of 6618 tons, settlement 0.56-1.68 cm and 3.32-3.64 cm, lateral deflection of 2.49 cm and 19.49 cm. The conclusion of the research indicates that the safe pile foundation used is 1000 mm group pile foundation. Keywords: Bearing Capacity; Foundations; Pile Foundation; Port Infrastructure; Settlement